PEMODELAN SISTEM KONTROL TRAFFIC LIGHT BERDASARKAN KEPADATAN KENDARAAN DENGAN TEKNIK EDGE DETECTION DAN LOGIKA FUZZY - Budi Sutomo (Jurnal Informatika, 2015)
In general, traffic control has been using traffic lights regulator. Use of Traffic Light has the disadvantage of setting the vehicle is not based on the real-time condition of the number of cars but by time .Utilization of digital image processing technology can be applied to the traffic light system is to detect the number of vehicles on each side of the road . The detection number of vehicles using edge detection is a way to detect the density of vehicles. This method is an object filtering method to retrieve information about the edges of objects in the form of binary data. While to produce a long time to be provided on each side of the traffic light then use fuzzy logic to the Min-Max method, as a parameter which is based on a comparison of solid vehicle of each side of the road.The results obtained, namely the amount of time lights of traffic light at each segment based intensiveness of vehicles, the solid vehicle, the green light lit up time is getting longer.keyword: Digital image processing, edge detection, fuzzy logic, real-time, traffic light.